Student Ability in Using Algebrator Software: Case Study During Online Learning - Aholongan, Anggi; Suripah, Suripah (Al-Khawarizmi, 2021)
Online learning as an alternative that can be applied during the Covid-19 period. For the sake of smooth online learning, teachers need to make innovations so that the concepts of abstract mathematics learning are easily understood by students. One alternative is the use of technology as a learning medium to help solve mathematical problems using Algebrator software. This study aims to describe the ability of students to use Algebrator Software on number material as an alternative to online learning based on their mastery in using Algebrator. This research qualitative descriptive research with a case study approach. The research subjects were 5 class VII students who were randomly selected. The results of this study indicate that the ability of students to use Algebrator Software on number material as an alternative to online learning has been sufficiently mastered based on the results of the tests given and supported by the results of interviews. It is hoped that in the future students can improve their ability to master technology in mathematics learning.